DO NOT WASTE WATER: OUR MOST PRECIOUS RESOURCE - Xusanboyeva Nodira,; Mannobov Abdumalik Mansurjon oʻgʻli, (TADQIQOTLAR, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, explores one of the most urgent environmental challenges of our time — the wasteful use of water. The author examines why water is considered our most precious  resource,  how  human  habits  are  causing  its  depletion,  and  what  every individual can do to conserve it. Drawing on examples from Uzbekistan and comparing them to water-scarce regions such as Africa, the article encourages young readers to reflect on their daily water use and take meaningful steps to protect this vital resource for future generations.